A literature of restitution : critical essays on W.G. Sebald - Baxter, Jeannette,Ed; Henitiuk, Valerie,Ed; Hutchinson, Ben,Ed (Manchester University Press, 2013)
"This book investigated the crucial question of 'restitution' in the work of W.G. Sebald. Written by a range of leading scholards from fields as various as translation studies, English, German, and comparative literature, photography, critical theory, psychoanalysis, poetry, and art theory, the essays collected in the volume place Sebald's oeuvre within the broader context of European culture in order to better understand his engagement with the ethics of aesthetics." -- Page 4 of cover.